Continuously applying compost for three years alleviated soil acidity and heavy metal bioavailability in a soil-asparagus lettuce system - Chen, De; Ye, Xuezhu; Jiang, Yugen; Xiao, Wendan; Zhang, Qi; Zhao, Shouping; Shao, Sainan; Gao, Na; Huang, Miaojie; Hu, Jing (Frontiers in Plant Science, 2022)
Soil acidification and heavy metal pollution are two common barrier factors threatening plant growth and agro-product quality. Applying manure compost is promising to alleviate soil acidity, while it may increase heavy metal accumulation in soil. In a three-year field experiment, compost was applied for 12 consecutive harvest seasons at 15, 30, and 45 t ha-1 in a slightly acidic soil. Samples were taken at the twelfth season to examine the changes of soil properties, vegetable productivity, heavy metal accumulation and bioavailability in the soil-asparagus lettuce system. The results showed that the pH values of the topsoil were increased by 0.49–0.75 units in compost added soils compared with no compost control, soil organic matter (SOM) contents and cation exchange capacity (CEC) were increased by 34%–101% and 43%–44%, respectively. The soil nutrient contents were also increased in compost treatments. Continuously applying compost increased Cd, Cu, and Zn concentrations in topsoil by up to 32%, 20%, and 22% and decreased Pb by 10%, while soil available Cd and Zn concentrations were reduced by up to 54% and 86%, and available Cu was increased by 19%–63%. The biomass of asparagus lettuce was increased by 30%–59% in compost treatments, with Cd and Zn concentrations in the plant tissues reduced by 28%–50% and 14%–67%. Cu concentrations in the lettuce shoots were increased by 20%–39%. The concentration factor and total uptake of Cd and Zn in lettuce were effectively reduced in compost treatments. Cd was more prone to be taken up, translocated and accumulated from soil to the lettuce plant than the other heavy metals. Continuously applying compost over three years increased soil pH, SOM, CEC, nutrient contents, and lettuce productivity, decreased Cd and Zn bioavailability in the soil-lettuce system, while posing a risk of increasing heavy metal accumulation in topsoil.